2014
DOI: 10.1136/annrheumdis-2014-205698
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the anticitrullinated peptide antibody response in relation to therapeutic outcome in early rheumatoid arthritis: results from the SWEFOT trial

Abstract: ObjectiveTo determine the relationship between changes in antibody levels towards citrullinated peptides derived from different candidate autoantigens and therapeutic outcome in early rheumatoid arthritis (RA).MethodsBaseline and 3-month serum samples from 316 patients with early RA enrolled in the Swedish Farmacotherapy (SWEFOT) trial were analysed for antibodies against cyclic citrullinated peptides (CCP) and citrullinated peptides derived from vimentin (cVim), fibrinogen (cFib) and α-enolase (CEP-1). At 3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 28 publications
5
26
1
1
Order By: Relevance
“…Also, Cambridge et al showed that both ACPA IgG and IgA decreased after rituximab treatment [25]. TNF inhibition seems to associate with ACPA reductions in early RA [29], but not in established disease [24,29]. Thus, reduced SC expression could lead to lower levels of SIgA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Cambridge et al showed that both ACPA IgG and IgA decreased after rituximab treatment [25]. TNF inhibition seems to associate with ACPA reductions in early RA [29], but not in established disease [24,29]. Thus, reduced SC expression could lead to lower levels of SIgA.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SC is dependent upon tumour necrosis factor (TNF) [27]-induced nuclear factor kappa B (NF-κB) activation [28]. TNF inhibition seems to associate with ACPA reductions in early RA [29], but not in established disease [24,29]. Hence, it would be relevant to study the impact of anti-TNF therapy regarding ACPA SIgA levels, but in the current study the statistical power was insufficient for investigation of any specific impact of bDMARDs on ACPA isotype response.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrate that ACPA appear up to several years before disease onset and predict RA development. Further, diversification with recognition of an increasing number of citrullinated peptides and concomitant rise in ACPA titres occur before disease onset,5 10 11 to reach a fairly stable repertoire once the RA classification criteria are fulfilled 13 14. A few small studies have been performed on individuals without signs and/or symptoms of the disease but at an elevated risk of developing arthritis (eg, symptom-free first-degree relatives of patients with RA), indicating lower titres and fewer ACPA reactivities as compared with their RA probands, but higher concentrations compared with population controls 8 15–18…”
Section: Introductionmentioning
confidence: 99%
“…The posttranslational shapes can be seen as antigens generating immune responses which results in the production of ACPAs with ≥95% specificity for RA [1]. Several studies confirm that the presence of ACPAs associates with accelerated bone erosions in RA [11][12][13]. To detect ACPAs, several assays have been developed, for instance employing filaggrin-derived peptides (CCP-assay), mutated citrullinated vimentin (MCV-assay), and viral citrullinated peptides (VCPassay).…”
Section: Preclinical Ramentioning
confidence: 99%